Overview of Keda Torus eXperiment initial results. (17th August 2017) - Liu, Wandong; Lan, Tao; Mao, Wenzhe; Li, Hong; Xie, Jinlin; Liu, Ahdi; Wan, Shude; Wang, Hai; Zheng, Jian; Wen, Xiaohui; Zhou, Haiyang; You, Wei; et al.
Abstract: The Keda Torus eXperiment (KTX) is a new reversed field pinch (RFP) device at the University of Science and Technology of China. The construction and assembly of KTX, including the vacuum chamber, conducting shell, magnetic field windings, power supply system, active control coils, vacuum pump and data acquisition system, have been completed on August 1, 2015. Immediately following that, the first plasma was obtained on August 15, 2015. Intensive conditioning of the machine is underway to ramp up the plasma current toward its full operation. An active feedback mode control system has been built and has been implemented to control the error field around the vertical gaps of the conducting shell. The pulsed power supply systems of ohmic heating field and toroidal field (TF), using thyristor and energy storage capacitors, have been tested and commissioned. The TF power supply has flexibility in being able to operate with a reversed TF configuration and stable TF configuration. The fundamental diagnostic tools are developed for early KTX operation. Currently, the plasma current is up to 205 kA and the maximum discharge length is 21 ms, approaching to the conducting shell penetration time. Furthermore, typical RFP discharges are being produced with RFP state lasting 2 ms. These initial operation results for KTX are described in detail.